Legal Remedies against State Funding Decisions in Slovakia - Hulkó , Gábor (Public Governance, Administration and Finances Law Review, 2016)
Legal remedies against decisions of central state administration or special administrative bodies instead of the standardly used appeal (which is more or less identical in all Visegrad states) special types of legal remedies step in, which can be still considered as ordinary remedies. In Slovakia, the standard legal remedy in administrative procedures is the appeal (in case of organs of central administration called remonstrance) regulated by Act no. 71/1976 on Administrative Proceedings, however in case of special organs this regulation is often overwritten by special rules and by special legal remedies. Latter mentioned – from a jurisprudential point of view - raising the question, whether they can really serve as a tool for a real legal remedy if they represent an effective tool of decision supervision. The following case study introduces the standard procedure of use of such special legal remedy against a decision of the State Fund for Housing Development in Slovakia.